Reperfusion of occluded branch retinal arteries by transluminal Nd:YAG laser embolysis combined with intravenous thrombolysis of urokinase - Chai, Fang (Biosci Rep, 2018)
Purpose: To report successful treatment with transluminal Nd:YAG laser embolysis (TYE) combined with urokinase thrombolysis for reperfusion of occluded branch retinal arteries with visible emboli. Methods: A total of 34 eyes from 34 patients with acute, severe vision loss secondary to a branch retinal artery occlusion with visible emboli and retinal whitening were examined. Each patient was administered TYE therapy, which focused on the embolus, using an ocular contact lens; a 0.3–0.9 mJ laser pulse was delivered directly and gradually according to the reaction. Fundus photographs and fundus fluorescein angiography (FFA) were obtained before and immediately after the laser treatment. All patients received urokinase thrombolysis therapy drops intravenously for 5 days at 10–20 u/d. The follow-up period ranged from 6 to 14 months after therapy. The morphological characteristics of FFA associated with obstruction recovery of arterial fluorescence filling and visual function were analyzed. Results: After TYE therapy, FFA examinations showed that the retinal artery and its branches exhibited completely restored blood flow without obstruction in 13 eyes, accounting for 38.2% of the cases. The blood flow was mostly recovered in 11 eyes (32.4% of patients). FFA examinations following the combined intravenous urokinase thrombolysis therapy showed that the retinal artery and its branches exhibited completely restored blood flow after obstruction in 16 eyes (47.1% of patients). The blood flow was mostly recovered in 15 eyes (44.1% of patients). Conclusion: TYE combined with urokinase thrombolysis is effective for reperfusion of occluded branch retinal arteries and improving visual recovery in patients with visible emboli.